Expression of TdT in Myoepithelial Cells: Investigation in Breasts, Sweat Glands, and Salivary Lesions Emphasizing the Never-Documented Immunohistochemical Findings. (October 2020) - Zhou, Jun; Xu, Haimin; Zeng, Hong; Ma, Hongjun; Yu, Jingjing; Liu, Xia; Sun, Zhulei; Zhou, Luting; Zheng, Saifang; Wang, Xue; Wang, Anran; Wang, Chaofu
Background . The expression of terminal deoxynucleotidyl transferase (TdT) in myoepithelial cells (MECs) within the breast was recently incidentally observed in our routine practice. This study aimed to elucidate the expression of TdT in MECs. Methods . TdT immunostaining was performed on 180 mammary, 89 cutaneous, and 94 salivary tissues or lesions. Other myoepithelial markers, including P63, calponin, and SMA as well as double staining for TdT and calponin, were also evaluated in some cases. Selected lesions with basal or myoid differentiation were also included in the investigation. Results . MECs were positive for TdT in mammary lesions that contained MECs (132/135) but negative when they did not contain MECs (45/45). MECs in sweat glands (24/30) and their neoplastic counterparts, including those in hidradenoma papilliferum (2/9), spiradenoma (6/6), and cutaneous mixed tumor (9/9), showed weak to moderate TdT positivity. MECs were variably immunolabeled for TdT in salivary or salivary gland–type tumors with myoepithelial differentiation (pleomorphic adenoma, 24/25; basal cell adenoma, 6/7; adenoid cystic carcinoma, 7/7; Warthin tumor, 0/6; mucoepidermoid carcinoma, 0/8; acinic cell carcinoma, 0/4), but MECs in normal salivary gland barely stained for TdT (30/32). Conclusions . Our findings indicate that TdT may be eligible as an additional auxiliary immunohistochemical marker as P63, but not a surrogate, to identify the MECs in the breast with limited cross-reactivity, particularly in lesions with a prominent proportion of MECs. Positivity for TdT, along with other relevant markers, in a subset of sweat gland lesions and salivary tumors may contribute to their diagnosis.